Effects of Size Grading and Different Stocking Size Compositions on Growth Performance of Hybrid Tilapia (Oreochromis niloticus♀ X Oreochromis aureus♂) Juvenile - Suat Dikel; Fırat Sertaç Tellioğlu (Turkish Journal of Agriculture: Food Science and Technology, 2020)
In aquaculture, size grading application is made in order to protect against the disadvantages caused by the length difference between fish. Via this activity, large and small individuals separate each other during the feeding period. In this study designed for this purpose, it was aimed to determine whether the large individuals added to the herd had an effect on the growth performance of small individuals in the culture of Oreochromis niloticus♀ x Oreochromis aureus♂ hybrids. In the experiment, 0 age 1-4 g hybrid juvenile which just complete the juvenile period were stocked as 40 fish / m³ in 500 l fibre tanks placed in a greenhouse and cultured for 75 days. The experimental groups were designed as a graded group (G1) containing 1 g small individual, 1 g + 2 g (G2), 1 g +3 g (G3) and 1 g + 4 g (G4). At the end of the study, it was observed that grading did not positively effect on the growth of tilapia hybrids. In contrast, it was revealed that small individuals (18,60 ± 0,33g) in the G2 group, which included large individuals, grew better than small individuals in the other groups. However, the G2 group reached a better FCR (1.39 ± 0.05) than the other groups. The best economic conversion rate was again achieved in the G2 group (11.12 ± 0.75). As a result, it was observed that the culture practice with individuals of different sizes had a positive effect on the development of hybrid tilapia juvenile, especially when juvenile were stocked as 1+2g stocking composition, as a result of well competition can be established and this situation had a positive effect on the production cost.